Characterization of seaweed polysaccharide-based bilayer films containing essential oils with antibacterial activity. (October 2021) - Zhang, Bin; Liu, Yang; Wang, Huanhuan; Liu, Wenhua; Cheong, Kit-leong; Teng, Bo
Abstract: The antibacterial seaweed polysaccharide-based bilayer films were developed, which consisted of sodium alginate and agar, and incorporated with six different essential oils (EOs). The effect of different EOs on the bilayer film properties was extensively investigated based on the antimicrobial activity, the physical, mechanical and microstructure properties of the films. Addition of EOs significantly enhanced the thickness and elongation at break of the films, while decreased the tensile strength. The bilayer film containing ginger EO exhibited obvious and longer-lasting antimicrobial activity compared to films contained other EOs. It was also proved that the ginger EO film exhibit the most uniform porous structure and high crystallinity by the SEM and X-ray diffraction. Although the incorporation of EOs reduced the thermal stability of films, the better maintenance effect of ginger EO to the thermal stability of the ginger EO film was observed. According to ginger EO contained plentiful monocyclic sesquiterpenoids (71.01%) with conjugation structures, ginger EO molecules would combine with sodium alginate-agar through the p-π conjugation. Thus, the functional properties revealed that ginger EO was more positive to the comprehensive performance of films, and the sodium alginate-agar bilayer film contained ginger EO exhibited a strong potential of use in food packaging. Highlights: Seaweed polysaccharide-based bilayer package films were consisted of agar and sodium alginate. Ginger EO exhibited obvious antimicrobial activity for seaweed polysaccharide-based film. Bilayer film structure play ed an important role in longer lasting antimicrobial activity. Ginger EO had stronger combination with film matrix through p π conjugation.